Platformized Halal Governance in Indonesia: Religious Authority, Consumer Citizenship, and Digital Public Legitimacy - Fathurohman (Pen Of Political Authority and Religion, 2026)
Halal has expanded in Indonesia from a narrow category of religious compliance into a public system of trust, legitimacy, and moral regulation shaped by state institutions, religious authorities, and digital intermediaries. In platform-mediated commerce, halal now influences not only market choice but also the public ordering of credibility, responsibility, and acceptable conduct. This article examines how halal operates as a platformized form of public authority in contemporary Indonesia. It adopts a qualitative, theory-driven approach that combines scholarship on halal governance, digital religion, political authority, and consumer citizenship. The analysis draws on academic literature, policy and regulatory materials, certification-related public information, media coverage, and platform-facing commercial and influencer content connected to halal discourse in Indonesia. Analytical attention is directed to regulatory authority, religious legitimacy, platform visibility, influencer mediation, reputational sanction, and consumer citizenship as interrelated mechanisms through which halal becomes publicly actionable. Halal emerges as a hybrid governance device in which state regulation, clerical legitimacy, platform circulation, and consumer practice jointly structure moral order in everyday market life. The article concludes that halal in digital Indonesia should be understood not merely as a market attribute but as a dispersed form of public power embedded in certification, visibility, and reputational governance. It contributes to current scholarship by providing an integrated framework for explaining how religion shapes political authority through platform-mediated consumption and how digital infrastructures reconfigure state–religion relations in everyday public life.